Investigating international time trends in the incidence and prevalence of atopic eczema 1990-2010: a systematic review of epidemiological studies. - Ivette A G Deckers; Susannah McLean; Sanne Linssen; Monique Mommers; C P van Schayck; Aziz Sheikh (PLoS ONE, 2012)
The prevalence of atopic eczema has been found to have increased greatly in some parts of the world. Building on a systematic review of global disease trends in asthma, our objective was to study trends in incidence and prevalence of atopic eczema. Disease trends are important for health service planning and for generating hypotheses regarding the aetiology of chronic disorders. We conducted a systematic search for high quality reports of cohort, repeated cross-sectional and routine healthcare database-based studies in seven electronic databases. Studies were required to report on at least two measures of the incidence and/or prevalence of atopic eczema between 1990 and 2010 and needed to use comparable methods at all assessment points. We retrieved 2,464 citations, from which we included 69 reports. Assessing global trends was complicated by the use of a range of outcome measures across studies and possible changes in diagnostic criteria over time. Notwithstanding these difficulties, there was evidence suggesting that the prevalence of atopic eczema was increasing in Africa, eastern Asia, western Europe and parts of northern Europe (i.e. the UK). No clear trends were identified in other regions. There was inadequate study coverage worldwide, particularly for repeated measures of atopic eczema incidence. Further epidemiological work is needed to investigate trends in what is now one of the most common long-term disorders globally. A range of relevant measures of incidence and prevalence, careful use of definitions and description of diagnostic criteria, improved study design, more comprehensive reporting and appropriate interpretation of these data are all essential to ensure that this important field of epidemiological enquiry progresses in a scientifically robust manner.